Activation of Invariant Natural Killer T Cells by α-Galactosylceramide Attenuates the Development of Angiotensin II-Mediated Abdominal Aortic Aneurysm in Obese ob/ob Mice - Saito, Akimichi; Ishimori, Naoki; Tokuhara, Satoshi; Homma, Tsuneaki; Nishikawa, Mikito; Iwabuchi, Kazuya; Tsutsui, Hiroyuki (Frontiers in Cardiovascular Medicine, 2021)
The infiltration and activation of macrophages as well as lymphocytes within the aorta contribute to the pathogenesis of abdominal aortic aneurysm (AAA). Invariant natural killer T (iNKT) cells are unique subset of T lymphocytes and have a crucial role in atherogenesis. However, it remains unclear whether iNKT cells are involved also in the development of AAA. Ob/ob mice were administered angiotensin II (AngII, 1000 ng/kg/min) or phosphate-buffered saline (PBS) by osmotic minipumps for 4 weeks and further divided into 2 groups; α-galactosylceramide (αGC, 0.1 μg/g body weight intraperitoneal injection; PBS-αGC; n=5 and AngII-αGC; n=12), which specifically activates iNKT cells, and PBS (PBS-PBS; n=10, and AngII-PBS; n=6). Maximal abdominal aortic diameter was comparable between PBS-PBS and PBS-αGC, and was significantly greater in AngII-PBS than in PBS-PBS. This increase was significantly ameliorated in AngII-αGC without affecting blood pressure. αGC significantly enhanced iNKT cell infiltration compared to PBS-PBS. The ratio of F4/80-positive macrophages or CD3-positive T lymphocytes area to the lesion area was significantly higher in AngII-PBS than in PBS-PBS, and was significantly decreased in AngII-αGC. Gene expression of M2-macrophage specific markers, arginase-1 and resistin-like alpha, was significantly greater in aortic tissues from AngII-αGC compared to AngII-PBS 1 week after AngII administration, and this increase was diminished at 4 weeks. Activation of iNKT cells by αGC can ameliorate AngII-mediated AAA in ob/ob mice via inducing anti-inflammatory M2 polarized state. Activation of iNKT cells by the bioactive lipid αGC may be a novel therapeutic strategy against the development of AAA.